2003
DOI: 10.1093/nar/gng078
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable and efficient mRNA templates for mRNA-protein fusions and C-terminally labeled proteins

Abstract: For high-throughput in vitro protein selection using genotype (mRNA)-phenotype (protein) fusion formation and C-terminal protein labeling as a post-selection analysis, it is important to improve the stability and efficiency of mRNA templates for both technologies. Here we describe an efficient single-strand ligation (90% of the input mRNAs) using a fluorescein-conjugated polyethylene glycol puromycin (Fluor-PEG Puro) spacer. This ligation provides a stable c-jun mRNA with a flexible Fluor-PEG Puro spacer for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
82
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 24 publications
0
82
0
Order By: Relevance
“…20 Briefly, the purified DNA was transcribed with a RiboMax large-scale RNA production system-SP6 (Promega). The resulting RNA was purified with an RNeasy mini kit (Qiagen) and ligated with polyethylene glycol (PEG)-Puro spacer [p(dCp) 2 -T(Fluor)p-PEGp-(dCp) 2 -puromycin] using T4 RNA ligase (Takara).…”
Section: Tgggcgagaccgctcgaggttc-3mentioning
confidence: 99%
See 1 more Smart Citation
“…20 Briefly, the purified DNA was transcribed with a RiboMax large-scale RNA production system-SP6 (Promega). The resulting RNA was purified with an RNeasy mini kit (Qiagen) and ligated with polyethylene glycol (PEG)-Puro spacer [p(dCp) 2 -T(Fluor)p-PEGp-(dCp) 2 -puromycin] using T4 RNA ligase (Takara).…”
Section: Tgggcgagaccgctcgaggttc-3mentioning
confidence: 99%
“…20,21 In the mRNA display technique, each mRNA in a library is covalently bound to its corresponding protein through puromycin, 22,23 but mRNA sequences containing a stop codon or frameshift cannot form mRNA-protein conjugates or cannot be properly translated to generate the C-terminal tag, respectively. Thus, they can be washed away in affinity selection based on a property of the peptide portion.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, the proteins have been expressed in Escherichia coli, purified to homogeneity, and then fluorescently labelled by chemical modification methods, but the expression and purification of large numbers of proteins is a daunting task. As an approach to overcome this problem, a simple method for in vitro fluorescencelabelling of proteins using a derivative of puromycin was developed in our laboratory (7)(8)(9)(10)(11)(12), and the method was also applied to the fluorescence labelling of newly synthesized proteins in living cells (13). Since our method relies on incorporation of a fluorescent puromycin analogue into the C-terminus of the full-length protein during protein synthesis on ribosomes, the expression and labelling steps are synchronized and a purification process before labelling is unnecessary.…”
Section: Introductionmentioning
confidence: 99%
“…The yield of fluorescently labelled proteins is enhanced by the use of mRNA without a stop codon (Fig. 1C) (7,10), but many cDNA collections contain stop codons and their elimination usually requires a large set of oligo DNA primers. Agafonov et al (14) reported that the inactivation of release factor 1 (RF1) leads to better incorporation of puromycin using template mRNA with a UAG stop codon (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Two approaches recently used to identify protein binding partners are mRNA display techniques, such as mRNA-protein fusions (17)(18)(19)(20)(21) and in vitro virus, based on cell-free co-translation and affinity selection (22)(23)(24) and tandem affinity purification (TAP)-mass spectrometry methods. These methods are well suited for identifying the components of complexes that form in near physiological conditions.…”
mentioning
confidence: 99%